Fred Claus [videorecording (Blu-Ray )] - Fogelman, Dan; Vaughn, Vince; Giamatti, Paul; Higgins, John Michael; Richardson, Miranda; Bates, Kathy, 1948-; Spacey, Kevin; Banks, Elizabeth, 1974-; Weisz, Rachel, 1970-; Beck, Christophe, 1972- (Warner Home Video, 2007)
Fred Claus has lived in his little brother's shadow for most of his life. Fred is in jail and Nicholas has to bail him out on the condition he come to the North Pole and repay his debt.